Trade Liberalization and Fight Against Poverty - Trabelsi, Mohamed Ali; Liouane, Naoufel (International Journal of Economics and Financial Issues, 2013)
The struggle against poverty and social inequality is one of the biggest challenges for developing countries. These countries should adapt themselves to a new economic world order characterized by trade liberalization and based on a desire to make globalization work for poorer people. Most empirical studies on the relationship between trade, inequality and poverty assume that trade contributes to increasing wage inequality in developing countries. In this paper, we studied the impact of trade liberalization on poverty on a sample of 106 developing countries during the period 1980-2010. The results indicate that trade is not the main factor affecting inequality and poverty persistence. Keywords: Social inequality; trade liberalization; globalization; poverty JEL Classifications: A13; F43; I32; O57